Discovery and vertical transmission analysis of Dabieshan Tick Virus in Haemaphysalis longicornis ticks from Chengde, China - Xu, Xiaofeng; Gao, Zhihua; Wu, Youhong; Yin, Hong; Ren, Qiaoyun; Zhang, Jie; Liu, Yongsheng; Yang, Shunli; Bayasgalan, Chimedtseren; Tserendorj, Ariunaa; Yang, Xiaolong; Chen, Ze (Frontiers in Microbiology, 2024)
Ticks are important blood-sucking ectoparasites that can transmit various pathogens, posing significant threats to the wellbeing of humans and livestock. In this study, we used the sRNA sequencing method to identify the DBTV in newly moulted Haemaphysalis longicornis adult ticks collected from Chengde, Hebei Province. The complete coding genome of Dabieshan Tick Virus (DBTV) were obtained through sRNA-seq and Sanger sequencing (OP682840 and OP716696). Additionally, DBTV was also detected in both unfed nymphs and engorged females of H. longicornis collected from Chengde, with a positive rate of 20% and 56.25%, respectively. The results of phylogenetic analysis revealed that DBTV Hebei strain clustered with previously reported DBTV strains.Notably, the Hebei strain was grouped together the Liaoning strain but lacks recorded S segment sequences. Further research is needed to investigate the mechanisms underlying the differentiation between these different groups. To gain a clearer understanding of the mode of DBTV transmission in ticks, we conducted a study on the transmission experiment of this virus from positive engorged females to larvae of the subsequent generation in laboratory for the first time. The results revealed that aside from engorged females, both eggs and larvae of the subsequent generation could also exhibit the presence of DBTV.Moreover, through the detection of DBTV in unfed nymphs and adults (which moulted from engorged nymphs) collected from Chengde, it can be concluded that H. longicornis serves as a potential transmission host and reservoir for DBTV through transstadial and transovarial transmission.